Bone implant with piezoelectric coating as well as preparation method and application of bone implant
By using a composite piezoelectric coating of barium titanate and titanium dioxide on the bone implant, and ultrasonic stimulation regulates the production of ROS and H2, the problem of difficulty in compatibility between antibacterial and oxidative stress removal functions in the prior art is solved, and effective antibacterial and bone regeneration effects are achieved.
Patent Information
- Application Number
- CN202411934691.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
Excessive reactive oxygen species (ROS) produced by existing bone implants in antibacterial treatment is difficult to control, resulting in bone tissue being in a state of high oxidative stress, and the prior art is difficult to compatible with antibacterial and oxidative stress removal functions.
Using a bone implant with a piezoelectric coating, the production of ROS and H2 is regulated under ultrasonic stimulation through a composite piezoelectric coating of barium titanate and titanium dioxide. High-power ultrasonic is used for antibacterial treatment, and low-power ultrasonic is used to clear excess ROS.
It has achieved effective removal of excessive ROS during the antibacterial process, reduced toxic side effects on bone tissue, promoted bone regeneration, and improved the effect of bone implant infection treatment.
Smart Images

Figure CN119733103A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of orthopedic biomaterials, and in particular to a bone implant with a piezoelectric coating, a preparation method and an application thereof. Background Art
[0002] Bone implant local infection is a chronic bone tissue infection disease caused by purulent bacteria, especially drug-resistant Staphylococcus aureus. It is complicated, has a long course of disease, and has a high treatment failure rate and recurrence rate. It is easy to lead to implant failure and further bone defects and infections. It is a major intractable disease in the field of orthopedics. At present, the main treatment for bone implant site infection is surgery combined with antibiotic treatment. However, surgery to replace the implant is a further harm to the patient. Secondly, the physiological toxicity of antibiotics should not be underestimated. Therefore, antibacterial methods based on external field response have been widely developed. This antibacterial method often functionalizes the surface of the bone implant through a series of surface modification methods to enable it to have antibacterial function under external field stimulation. Sonodynamic antibacterial (SDT) is one of them. However, the reactive oxygen species (ROS) generated by SDT are not controllable, and excessive ROS are often generated, which puts the bone tissue site in a state of high oxidative stress after antibacterial treatment. Most of the existing technologies only focus on the antibacterial effect in bone implant infection, or simply the function of removing oxidative stress, and fail to well combine "antibacterial" and "removing oxidative stress". Such technologies with relatively single functions cannot meet the needs of bone implant infection treatment.
[0003] Therefore, it is of great significance to construct a bone implant material that can realize SDT function and clear the excess ROS generated by SDT after SDT. Summary of the invention
[0004] In view of this, the present invention provides a bone implant with a piezoelectric coating and a preparation method and application thereof, so as to solve or at least partially solve the defects existing in the prior art.
[0005] In a first aspect, the present invention provides a bone implant with a piezoelectric coating, comprising a substrate and a piezoelectric coating located on the surface of the substrate, wherein the piezoelectric coating is a composite piezoelectric coating of barium titanate and titanium dioxide.
[0006] Preferably, the barium titanate is in tetragonal phase, and the titanium dioxide is brookite-type titanium dioxide.
[0007] Preferably, the material of the substrate is any one of metal, metal alloy, cemented carbide, silicon, glass, and polymer.
[0008] Preferably, the metal includes any one of titanium, gold, platinum, niobium and tantalum;
[0009] The metal alloy includes any one of titanium-based alloy, cobalt-based alloy, nickel-based alloy and stainless steel;
[0010] The cemented carbide includes any one of tungsten carbide-based cemented carbide, titanium carbide-based cemented carbide, titanium carbonitride-based cemented carbide, and chromium carbide-based cemented carbide.
[0011] In a second aspect, the present invention further provides a method for preparing the bone implant with a piezoelectric coating, comprising the following steps:
[0012] The barium carbonate and titanium dioxide are mixed and ball-milled to obtain a mixed powder;
[0013] adding polyvinyl alcohol aqueous solution to the mixed powder, drying, grinding, and sieving to obtain spray powder;
[0014] The spray powder is sprayed on a substrate by a plasma spraying method to obtain a bone implant with a piezoelectric coating.
[0015] Preferably, the process parameters of the plasma spraying method include: argon flow rate of 40-60 L / min, hydrogen flow rate of 10-15 L / min, spraying power of 35-45 kW, spraying distance of 80-120 mm, and powder feeding rate of 18-25 g / min.
[0016] Preferably, the molar ratio of barium carbonate to titanium dioxide is 1:(1-3);
[0017] The ball milling medium used in the ball milling is zirconium oxide grinding beads;
[0018] The ratio of the sum of the mass of the barium carbonate and the titanium dioxide to the mass of the ball milling medium is 1:(1-1.5);
[0019] The ball milling speed is 350-400 r / min, and the ball milling time is 4-6 hours.
[0020] Preferably, in the step of adding the polyvinyl alcohol aqueous solution to the mixed powder, the mass concentration of the polyvinyl alcohol aqueous solution is 10-15%, and the mass of the polyvinyl alcohol aqueous solution is 5-10% of the mass of the mixed powder.
[0021] Preferably, the spray powder has a mesh size of 80 to 200 meshes.
[0022] In a third aspect, the present invention also provides an application of the bone implant with a piezoelectric coating or the bone implant with a piezoelectric coating prepared by the preparation method in the preparation of biomaterials that promote bone regeneration or in the generation of ROS or H2 under the action of ultrasound.
[0023] The bone implant with piezoelectric coating and its preparation method and application of the present invention have the following beneficial effects compared with the prior art:
[0024] 1. The bone implant with piezoelectric coating of the present invention utilizes the piezoelectric properties of BTO and the heterojunction function constructed by TiO2, so that the coating itself has a high response function under US, and has SDT and hydrogen production performance under ultrasound. By changing the ultrasonic power to affect its function, the influence of its function under US is different. In the early stage of treatment, due to the severity of bacterial infection, high-power US stimulation is preferred. The material will respond to US and produce a large amount of ROS to kill bacteria and achieve antibacterial function. After the antibacterial process is completed, since the large amount of ROS produced by antibacterial will have toxic side effects on cells, low-power US stimulation is used at this time to achieve the function of more H2 production, thereby removing the above-mentioned excess ROS, achieving the purpose of antibacterial, neutralizing excess ROS, and promoting bone regeneration;
[0025] 2. The preparation method of the bone implant with piezoelectric coating of the present invention utilizes the physical properties of BTO and TiO2 to mix BTO and TiO2 for spraying, and obtains the BTO@TiO2 structure of target parameters by constructing a heterojunction structure based on BTO material and adjusting different spraying parameters and material ratios. The structure has tetragonal BTO and brookite-type TiO2, and has good piezoelectric properties. By adjusting different ultrasonic stimulation parameters, it is finally obtained that under high-power ultrasonic stimulation, the material is more inclined to produce ROS and can be used for antibacterial treatment, and under low-power ultrasonic stimulation, the material is more inclined to produce H2, which can be used to remove excess ROS. The technical process of the present invention is simple, highly repeatable, and is expected to achieve large-scale production. The prepared piezoelectric coating, while playing an antibacterial role, can not only neutralize the toxic and side effects of excessive ROS generated by acoustic power on cells in the later stage, but also reshape the bone regeneration microenvironment, taking into account the function of promoting bone regeneration, and has great potential for the effective treatment of bone implant infection. The piezoelectric coating prepared by the present invention has various properties such as antibacterial, oxidative stress removal, bone regeneration microenvironment remodeling, and bone regeneration promotion, so as to improve the treatment effect of bone implant infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 This is a surface scanning electron microscopy image of the bone implant BTO@TiO2 with a piezoelectric coating prepared in Example 1;
[0028] Figure 2 Element mapping of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1;
[0029] Figure 3 This is the Ba element distribution diagram of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1;
[0030] Figure 4 This is the Ti element distribution diagram of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1;
[0031] Figure 5 This is the C element distribution diagram of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1;
[0032] Figure 6 This is the O element distribution diagram of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1;
[0033] Figure 7 The XRD pattern of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1;
[0034] Figure 8 Schematic diagram of the degradation of MV and DPBF by the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, P-BTO prepared in Comparative Example 1, and ordinary titanium alloy TC4;
[0035] Fig. 9 Schematic diagram of H2 generation capability of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, P-BTO prepared in Comparative Example 1, and ordinary titanium alloy TC4;
[0036] Fig.10 Schematic diagram of the antibacterial properties of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, the P-BTO prepared in Comparative Example 1, and the common titanium alloy TC4;
[0037] Fig.11 Bacterial plating diagram of the antibacterial properties of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, the P-BTO prepared in Comparative Example 1, and the common titanium alloy TC4;
[0038] Fig.12 Live-dead staining diagrams of the antibacterial properties of the bone implant BTO@TiO2 with a piezoelectric coating prepared in Example 1, the P-BTO prepared in Comparative Example 1, and the common titanium alloy TC4;
[0039] Fig.13The graphs are the test results of the biocompatibility of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, the P-BTO prepared in Comparative Example 1, and the common titanium alloy TC4 to mouse embryonic osteoblast precursor cells;
[0040] Fig.14 The graphs are the test results of the biocompatibility of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, the P-BTO prepared in Comparative Example 1 and the common titanium alloy TC4 to mouse embryonic osteoblast precursor cells after ultrasonic stimulation;
[0041] Fig.15 This is a test chart of the ability of common titanium alloy TC4 to clear oxidative stress of mouse embryonic osteoblast precursor cells;
[0042] Fig.16 This is a test chart of the ability of P-BTO prepared in Comparative Example 1 to clear oxidative stress of mouse embryonic osteoblast precursor cells;
[0043] Fig.17 This is a test chart of the ability of the bone implant BTO@TiO2 with a piezoelectric coating prepared in Example 1 to clear oxidative stress in mouse embryonic osteoblast precursor cells. DETAILED DESCRIPTION
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The following are described in detail. It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.
[0046] The invention provides a bone implant with a piezoelectric coating, comprising a substrate and a piezoelectric coating located on the surface of the substrate, wherein the piezoelectric coating is a composite piezoelectric coating of barium titanate and titanium dioxide.
[0047] The bone implant with piezoelectric coating of the present invention is a composite piezoelectric coating of barium titanate and titanium dioxide. The perovskite material barium titanate (BTO) is a material with good ferroelectric properties, which can realize the generation of ROS under ultrasound (US) and can also generate H2 under US. The present invention utilizes the piezoelectric properties of BTO and the heterojunction function constructed by TiO2, so that the coating itself has a high response function under US, and has SDT and hydrogen production performance under ultrasound, and changes the ultrasonic power to affect its function, so that the effect of its function under US is not the same. In the early stage of treatment, due to the severity of bacterial infection, high-power US stimulation is preferentially used, and the material will respond to US to generate a large amount of ROS to kill bacteria and achieve antibacterial function. After the antibacterial process is completed, since the antibacterial generation of a large amount of ROS will have toxic side effects on cells, low-power US stimulation is used at this time to achieve the function of more H2 generation, thereby removing the above-mentioned excessive ROS, achieving the purpose of antibacterial, neutralizing excessive ROS, and promoting bone regeneration.
[0048] In some embodiments, the barium titanate is in a tetragonal phase and the titanium dioxide is brookite titanium dioxide.
[0049] The piezoelectric coating of the present invention comprises tetragonal BTO and brookite-type TiO2 and has good piezoelectric properties.
[0050] In some embodiments, the material of the substrate is any one of metal, metal alloy, cemented carbide, silicon, glass, and polymer.
[0051] In some embodiments, the metal includes any one of titanium, gold, platinum, niobium, and tantalum.
[0052] In some embodiments, the metal alloy includes any one of a titanium-based alloy (such as TC4, the composition of the titanium alloy TC4 material is Ti-6Al-4V), a cobalt-based alloy (such as cobalt-chromium alloy), a nickel-based alloy, and stainless steel.
[0053] In some embodiments, the cemented carbide includes any one of tungsten carbide-based cemented carbide, titanium carbide-based cemented carbide, titanium carbonitride-based cemented carbide, and chromium carbide-based cemented carbide.
[0054] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned bone implant with a piezoelectric coating, comprising the following steps:
[0055] S1, mixing barium carbonate and titanium dioxide, and ball milling to obtain a mixed powder;
[0056] S2, adding polyvinyl alcohol aqueous solution to the mixed powder, drying, grinding, and sieving to obtain spray powder;
[0057] S3. Spraying the spray powder onto a substrate using a plasma spraying method to obtain a bone implant having a piezoelectric coating.
[0058] Most of the existing technologies only focus on the antibacterial effect in bone implant infection, or the function of simply removing oxidative stress, and fail to well combine "antibacterial" and "removing oxidative stress". Such technologies with relatively single functions cannot meet the needs of bone implant infection treatment. Therefore, how to combine the two functions of BTO into one and exert their efficacy is the difficulty and innovation of the invention. Based on the current status of the treatment of bone implant infection, the present invention uses the physical properties of BTO and TiO2 to mix BTO and TiO2 for spraying, and obtains the target parameter BTO@TiO2 structure by constructing a heterojunction structure based on BTO material and adjusting different spraying parameters and material ratios. The structure has tetragonal BTO and brookite-type TiO2, and has good piezoelectric properties. By adjusting different ultrasonic stimulation parameters, it is finally obtained that under high-power ultrasonic stimulation, the material is more inclined to produce ROS, which can be used for antibacterial treatment, and under low-power ultrasonic stimulation, the material is more inclined to produce H2, which can be used to remove excess ROS. The technical process of the present invention is simple, repeatable, and is expected to achieve large-scale production. The prepared piezoelectric coating, while playing an antibacterial role, can not only neutralize the toxic side effects of excessive ROS generated by acoustic dynamics on cells in the later stage, but also reshape the bone regeneration microenvironment, taking into account the function of promoting bone regeneration, and has great potential for the effective treatment of bone implant infection. The piezoelectric coating prepared by the present invention has various properties such as antibacterial, removing oxidative stress, reshaping the bone regeneration microenvironment, and promoting bone regeneration, so as to improve the treatment effect of bone implant infection.
[0059] In the specific above embodiments, plasma spraying is a thermal spraying process, and during spraying, barium carbonate and titanium dioxide react to obtain barium titanate.
[0060] In some embodiments, the process parameters of the plasma spraying method include: argon flow rate of 40-60 L / min, hydrogen flow rate of 10-15 L / min, spraying power of 35-45 kW, spraying distance of 80-120 mm, and powder feeding rate of 18-25 g / min.
[0061] In some embodiments, the molar ratio of barium carbonate to titanium dioxide is 1:(1-3);
[0062] The ball milling media used in ball milling are zirconium oxide grinding beads;
[0063] The ratio of the sum of the mass of barium carbonate and titanium dioxide to the mass of the ball milling medium is 1:(1-1.5);
[0064] The rotation speed during ball milling is 350-400 r / min, and the ball milling time is 4-6 h.
[0065] In some embodiments, the zirconium oxide grinding beads include three types of grinding beads with diameters of 5-6 mm, 3-4 mm, and 1-2 mm; further, the mass ratio of the three types of grinding beads with diameters of 5-6 mm, 3-4 mm, and 1-2 mm is (1-2):(2-3):(4-5), and barium carbonate and titanium dioxide can be ground very evenly by using grinding beads of different diameters and masses.
[0066] In some embodiments, barium carbonate and titanium dioxide are mixed, zirconium oxide grinding beads are added, and then anhydrous ethanol is added, and the mixture is placed in a planetary ball mill for ball milling. After ball milling, the mixed solution of the powder and anhydrous ethanol is taken out and placed in an oven for drying at 80-100° C. for 4-6 hours to obtain a mixed powder of barium carbonate and titanium dioxide; (60-100) g: (40-60) g: (200-250) mL of barium carbonate, titanium dioxide, and anhydrous ethanol.
[0067] In some embodiments, in the step of adding polyvinyl alcohol aqueous solution to the mixed powder, the mass concentration of the polyvinyl alcohol aqueous solution is 10-15%, and the mass of the polyvinyl alcohol aqueous solution is 5-10% of the mass of the mixed powder.
[0068] In some embodiments, the mesh size of the spray powder is 80-200 mesh.
[0069] In some embodiments, a polyvinyl alcohol aqueous solution is added to the mixed powder, dried at 80-100° C. for 4-6 hours, ground, and sieved through a 80-200 mesh sieve to obtain a spray powder.
[0070] The preparation method of the bone implant with a piezoelectric coating of the present invention can use raw materials that can be directly purchased commercially, are conventional, low-priced, economical and practical; the present invention does not need to perform any modification or purification on the raw materials, can be used directly, is simple to operate, has strong repeatability, and has mass production value; the piezoelectric coating prepared by the present invention can not only play an antibacterial role, but also neutralize the toxic and side effects of a large amount of ROS generated by SDT antibacterial on bone regeneration-related cells in the later stage, and can also take into account the function of promoting bone regeneration; the present invention can effectively take into account both the "antibacterial" and "oxidative stress removal" functions, and has broad application prospects in the biomedical field.
[0071] Based on the same inventive concept, the present invention also provides an application of the above-mentioned bone implant with piezoelectric coating or the bone implant with piezoelectric coating prepared by the above-mentioned preparation method in the preparation of biomaterials that promote bone regeneration or the application of generating ROS or H2 under the action of ultrasound.
[0072] Specifically, the bone implant with piezoelectric coating of the present invention is subjected to high power (such as 3w / cm 2 ) Under ultrasound stimulation, the material is more inclined to produce ROS, which can be used for antibacterial treatment. 2 )Under ultrasonic stimulation, the material is more inclined to produce H2, which can be used to remove excess ROS.
[0073] The bone implant with piezoelectric coating of the present application and its preparation method and application are further described below with specific embodiments. This part further illustrates the content of the present invention in conjunction with specific embodiments, but should not be construed as limiting the present invention. If not specifically stated, the technical means adopted in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment adopted in the present invention are conventional reagents, methods and equipment in the art.
[0074] Example 1
[0075] The present application embodiment provides a bone implant with a piezoelectric coating, comprising the following steps:
[0076] S1, 78.9344g (0.4mol) of barium carbonate and 47.9196g (0.6mol) of titanium dioxide were mixed, 27.18g of zirconium oxide grinding beads with a diameter of 5mm, 54.36g of zirconium oxide grinding beads with a diameter of 3mm, and 108.725g of zirconium oxide grinding beads with a diameter of 1mm were added, and then 200ml of anhydrous ethanol was added, and the mixture was placed in a planetary ball mill at a speed of 35r / min and a ball milling time of 4h. After ball milling, the mixed solution of the powder and anhydrous ethanol was taken out, and placed in an oven to dry at 80°C for 4h to obtain a mixed powder of barium carbonate and titanium dioxide;
[0077] S2, add a polyvinyl alcohol aqueous solution with a mass concentration of 10% to the mixed powder in S1, dry at 80°C for 4 hours, grind, and sieve to obtain a spray powder; the average mesh size of the spray powder is 140 mesh; the mass of the polyvinyl alcohol aqueous solution is 10% of the mass of the mixed powder;
[0078] S3, spraying the spray powder in S2 on the substrate by plasma spraying to form a piezoelectric coating, thereby obtaining a bone implant with a piezoelectric coating (denoted as BTO@TiO2); the substrate is a titanium alloy TC4 with a thickness of 1 mm;
[0079] The process parameters of the plasma spraying method include: argon flow rate of 40 L / min, hydrogen flow rate of 10 L / min, spraying power of 40 kW, spraying distance of 120 mm, powder feeding rate of 18 g / min, and spraying time of 20 min.
[0080] This comparative example provides a bone implant with a barium titanate coating, comprising the following steps:
[0081] S1. Weigh 126.854 g of barium titanate, add 27.18 g of zirconia grinding beads with a diameter of 5 mm, 54.36 g of zirconia grinding beads with a diameter of 3 mm, and 108.725 g of zirconia grinding beads with a diameter of 1 mm, then add 200 ml of anhydrous ethanol, place in a planetary ball mill, rotate at 35 r / min, ball milling time 4 h, take out the mixed solution of powder and anhydrous ethanol after ball milling, put it in an oven and dry it at 80 ° C for 4 h to obtain barium titanate powder;
[0082] S2, add a polyvinyl alcohol aqueous solution with a mass concentration of 10% to the barium titanate powder in S1, dry at 80°C for 4 hours, grind, and sieve to obtain a spray powder; the average mesh size of the spray powder is 140 mesh; the mass of the polyvinyl alcohol aqueous solution is 10% of the mass of the barium titanate powder;
[0083] S3, spraying the spray powder in S2 on a substrate by plasma spraying to form a barium titanate coating, thereby obtaining a bone implant having barium titanate (denoted as P-BTO); the substrate is a titanium alloy TC4 with a thickness of 1 mm;
[0084] The process parameters of the plasma spraying method include: argon flow rate of 40 L / min, hydrogen flow rate of 10 L / min, spraying power of 40 kW, spraying distance of 120 mm, powder feeding rate of 18 g / min, and spraying time of 20 min.
[0085] Performance Testing
[0086] Figure 1 This is a surface scanning electron microscopy image of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1.
[0087] Figures 2 to 6 Element distribution (mapping) diagram of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1.
[0088] In order to determine whether the BTO-TiO2 composite piezoelectric coating prepared in the present invention has good melting degree and porosity, the BTO-TiO2 composite piezoelectric coating was characterized by SEM. The results showed that the obtained composite piezoelectric coating has good melting degree, its porosity is also relatively good, its mixing is uniform, and the element distribution is also very uniform.
[0089] Figure 7 This is the XRD pattern of the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1.
[0090] The BTO-TiO2 composite piezoelectric coating prepared in Example 1 was characterized by XRD analysis to determine that tetragonal BTO and brookite-type TiO2 were obtained. Figure 7 The XRD results show that the BTO-TiO2 composite piezoelectric coating prepared in the present invention can contain tetragonal BTO (ie, tetragonal BaTiO3 (p4mm)) and Brookite-type TiO2.
[0091] Study on the generation of ROS and H2 by bone implants with piezoelectric coating
[0092] Specifically, use 3w / cm 2 The ability of US to generate ROS was verified by 1w / cm 2 The ability of the material to produce hydroxyl radicals (·OH) was verified by US stimulation. The ability of the material to produce hydroxyl radicals (·OH) was verified by 20 mM methyl violet (MV) solution, and the ability of the material to produce hydroxyl radicals (·OH) was detected by 8 mM DPBF (1,3-diphenylisobenzofuran) solution. 1 O2's capabilities.
[0093] The bone implant (P-BTO) with pure barium titanate coating Pure-BTO and ordinary titanium alloy (TC4) prepared in Comparative Example 1 were used as controls; the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, P-BTO in Comparative Example 1, and titanium alloy (TC4) were respectively spread in 24-well plates, and 2 ml of MV solution or DPBF solution was dropped into each well plate, and 3 w / cm 2 US(3w / cm 2 After stimulation with 50% duty cycle and 1 MHz frequency, the UV-visible absorption spectra were tested respectively. The absorbance at the absorption wavelengths of 420nm and 580nm was compared and qualitatively analyzed. The results are as follows Figure 8 shown.
[0094] Figure 8 a in the figure is the ability to degrade MV. Figure 8 In a, C0 is the initial concentration of MV solution, and C is the concentration of MV solution after US stimulation at different times; Figure 8 b in the figure is the ability to degrade DPBF. Figure 8 In b, C0 is the initial concentration of DPBF solution, and C is the concentration of DPBF solution after US stimulation at different times. Figure 8 TC4 represents titanium alloy, BTO@TiO2 represents the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, and BTO represents P-BTO in Comparative Example 1.
[0095] from Figure 8It can be seen that the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1 has the best effect of degrading DPBF and MV compared with P-BTO and titanium alloy TC4 in Comparative Example 1, and has good ·OH and 1 O2 generation capacity; while the bone implant P-BTO with barium titanate coating prepared in Comparative Example 1 does not have good ·OH and 1 The TC4 coating in the control group had only trace amounts of ·OH and 1 The ability to produce O2 is due to the cavitation effect of ultrasound.
[0096] The bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1, P-BTO in Comparative Example 1, and titanium alloy (TC4) were respectively placed in a 24-well plate, and 2 ml of PBS (pH 7.3) was dropped into each well plate. 2 US(1w / cm 2 , 1mHZ, 50% duty cycle) stimulation, while no US stimulation and only PBS as a comparison, the air above the liquid was extracted using a gas sampling needle, and the concentration of different gases in the gas was calibrated by gas chromatography with or without ultrasound, and the generated gas was analyzed; the results are shown in Fig. 9 shown.
[0097] Fig. 9 BTO@TiO2(US) in Example 1 is subjected to 1w / cm 2 US stimulation, BTO@TiO2(Non US) means that BTO@TiO2 in Example 1 was not subjected to US stimulation; BTO(US) means that P-BTO in Comparative Example 1 was subjected to 1w / cm 2 BTO (Non US) means that the P-BTO in Comparative Example 1 was not subjected to US stimulation; TC4 (US) means that the titanium alloy TC4 was subjected to 1w / cm 2 US stimulation, TC4 (Non US) means that titanium alloy TC4 was not subjected to US stimulation; Only US means that a simple PBS solution (without adding other materials) was subjected to 1w / cm 2 US stimulation.
[0098] from Fig. 9 It can be seen that the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1 has good H2 generation ability, the bone implant P-BTO with barium titanate coating prepared in Comparative Example 1 does not have good H2 generation ability, and the control group TC4 has only weak H2 generation ability.
[0099] Study on the antibacterial properties of bone implants with piezoelectric coatings
[0100] Research on antibacterial properties, including:
[0101] a. Prepare TSB liquid medium and solid agar medium plates.
[0102] TSB liquid medium: Dissolve 15 g of tryptone soy broth in 500 mL of deionized water.
[0103] After high temperature sterilization (121°C, 20 min), cool and store in a 4°C refrigerator for later use;
[0104] Solid agar medium plate: Weigh 33g of nutrient agar and dissolve it in 1L of deionized water. After high-temperature sterilization (121℃, 20min), put it into a bacterial clean bench for UV irradiation for 30min, then pour the liquid culture medium into a culture dish (20ml), solidify it under UV light, and then put it upside down in a 4-degree refrigerator for storage.
[0105] b. Activation of bacteria
[0106] Use an inoculation loop to pick a certain amount of bacteria and streak them on the sterilized plate. Then culture them at 37℃ for 24 hours and use them in the experiment.
[0107] c. Bacterial activity evaluation (MTT) method
[0108] Pick the bacteria into PBS, vortex to mix, take 150uL of bacterial solution into a 96-well plate, and use PBS as a control. Measure the OD value at 530nm on an ELISA reader. The OD value is 0.1 and the bacterial density is 10 8 CFU / mL. Prepare the desired concentration using TSB medium.
[0109] In order to verify whether the BTO-TiO2 composite piezoelectric coating has antibacterial properties, Staphylococcus aureus, a common bacterial species in clinical osteomyelitis, was selected to detect the antibacterial properties of the particles: 1×105 CFU / ml Staphylococcus aureus liquid and 1 ml of bacterial culture medium (i.e., the TSB liquid culture medium prepared above) were co-cultured with the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1 in a 24-well plate. After culturing in a bacterial incubator at 37°C for 24 hours, the particles were subjected to a power of 3 W / cm 2, 50% duty cycle, 1 MHz frequency ultrasonic stimulation for 10 minutes, then carefully discard the supernatant, add 400 microliters of thiazolyl blue (MTT) solution (PBS solution containing 0.5 mg / mL MTT) to each well, incubate in a 37°C incubator for 2 hours, discard the supernatant, add an equal volume of dimethyl sulfoxide (DMSO), shake and mix on a horizontal shaker for 20 minutes, transfer to a 96-well plate, and read the absorbance at 570 nm to reflect the proliferation of bacteria. At the same time, P-BTO in Comparative Example 1 and titanium alloy (TC4) were used instead of BTO@TiO2, and no coating material was added. The same method was used for the above-mentioned power of 3w / cm 2 , 50% duty cycle, 1 MHz frequency ultrasound stimulation for 10 min as control; further, according to the same method as above, no ultrasound stimulation was performed for comparison; the results are as follows Fig.10 shown.
[0110] Fig.10 TC4 means that the titanium alloy TC4 was not subjected to US stimulation, Pure BTO means that the P-BTO in Comparative Example 1 was not subjected to US stimulation, BTO@TiO2 means that the BTO@TiO2 in Example 1 was not subjected to US stimulation, and TC4+US means that the titanium alloy TC4 was subjected to US stimulation (power 3w / cm 2 , duty cycle 50%, frequency 1 MHz ultrasonic stimulation), Pure BTO + US means that the P-BTO in Comparative Example 1 is subjected to US stimulation (power 3 w / cm 2 , duty cycle 50%, frequency 1 MHz ultrasonic stimulation), BTO@TiO2+US means that the BTO@TiO2 in Example 1 is subjected to US stimulation (power 3 w / cm 2 , duty cycle 50%, frequency 1 MHz ultrasonic stimulation), US means US stimulation of blank control without any coating material (power 3 w / cm 2 , duty cycle 50%, frequency 1 MHz ultrasonic stimulation).
[0111] from Fig.10 It can be seen that the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1 completely inhibited the growth of Staphylococcus aureus, the bone implant P-BTO with barium titanate coating prepared in Comparative Example 1 could not completely inhibit the growth of Staphylococcus aureus, and the control group TC4 did not show antibacterial properties.
[0112] To further verify the antibacterial properties of each coating, the dilution plate method was used to more clearly observe the antibacterial properties of the coating materials. 5CFU / ml of Staphylococcus aureus liquid and bacterial culture medium (i.e., the TSB liquid culture medium prepared above) were co-cultured with the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1 in a 24-well plate. After culturing in a bacterial incubator at 37°C for 24 hours, the power was 3w / cm 2 , 50% duty cycle, 1 MHz frequency ultrasonic stimulation for 10 min. Then carefully remove the supernatant, transfer the material to a 50 ml centrifuge tube, add 1 ml PBS solution, vortex to shake the bacteria off the surface of the material, and dilute the bacteria with PBS for 10 5 times, and then 100 μL was evenly spread on an agar plate (i.e., the solid agar medium plate prepared above), and placed in an incubator at 37°C for 24 hours, and then photographed and counted the number of bacteria using a colony analyzer to reflect the proliferation of bacteria; at the same time, P-BTO in Comparative Example 1 and titanium alloy (TC4) were used instead of BTO@TiO2, and the power was 3 w / cm 2 , 50% duty cycle, 1 MHz frequency ultrasound stimulation for 10 min as control; further, according to the same method as above, no ultrasound stimulation was performed for comparison; the results are as follows Fig.11 shown.
[0113] Fig.11 US(-) indicates no ultrasound stimulation; US(+) indicates ultrasound stimulation. Fig.11 TC4 represents titanium alloy TC4, BTO represents P-BTO in Comparative Example 1, and BTO@TiO2 represents BTO@TiO2 in Example 1.
[0114] Furthermore, using 1×10 5 CFU / ml of Staphylococcus aureus liquid and bacterial culture medium (i.e., the TSB liquid culture medium prepared above) were co-cultured with the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1 in a 24-well plate. After culturing in a bacterial incubator at 37°C for 24 hours, the power was 3w / cm 2 , 50% duty cycle, 1 MHz frequency ultrasonic stimulation for 10 min. Then carefully remove the supernatant, transfer the material to a 50 ml centrifuge tube, add 1 ml PBS solution, vortex to shake the bacteria off the surface of the material, and dilute the bacteria with PBS for 10 5times, then 100 μL was evenly spread on an agar plate (i.e., the solid agar medium plate prepared above), placed in an incubator at 37°C for 24 h, and then a mixture of SYTO-9 and PI dyes was added, gently mixed, (the concentrations of SYTO-9 and PI were 5 μM and 30 μM, respectively), incubated for 30 minutes under light-proof conditions, and observed using an inverted microscope; at the same time, P-BTO in Comparative Example 1 and titanium alloy (TC4) were used instead of BTO@TiO2, and the experiment was carried out in the same manner as above, and the results were as follows Fig.12 shown. Fig.12 TC4 represents titanium alloy TC4, BTO represents P-BTO in Comparative Example 1, and BTO@TiO2 represents BTO@TiO2 in Example 1.
[0115] Specifically, Fig.12 Live bacteria: intact membrane, SYTO-9 penetrates cells and binds to DNA → green fluorescence; dead bacteria: damaged membrane, PI enters cells and binds to DNA → red fluorescence, while inhibiting the fluorescence of SYTO-9; green fluorescence signal → live cells (SYTO-9), red fluorescence signal → dead cells (PI); through the combination of SYTO-9 and PI, the distribution and proportion of live and dead bacteria can be quickly and intuitively distinguished.
[0116] from Figures 11-12 It can be seen that the bone implant BTO@TiO2 with piezoelectric coating prepared in Example 1 completely inhibited the growth of Staphylococcus aureus, the bone implant P-BTO with barium titanate coating prepared in Comparative Example 1 could not completely inhibit the growth of Staphylococcus aureus, and the control group TC4 did not show antibacterial properties.
[0117] Biocompatibility of bone implants with piezoelectric coatings
[0118] The biocompatibility of titanium alloy TC4, P-BTO in comparative example 1, and BTO@TiO2 in example 1 was detected. Specifically, mouse embryonic osteoblast precursor cells (MC3T3-E1), which play an important role in the bone repair process, were co-cultured with titanium alloy TC4, P-BTO in comparative example 1, and BTO@TiO2 in example 1. CCK8 was used to detect the activity of the cells after 3 days / 7 days, and a blank control without any coating material was used as a comparison. The results are as follows: Fig.13 Further, in order to verify that US has no significant effect on the whole process, 1w / cm2 of 10min was added during the co-culture of MC3T3-E1 and BTO@TiO2 in Example 1. 2 US stimulation (1w / cm 2, duty cycle 50%, frequency 1 MHz), and then statistically analyzed its biocompatibility under US stimulation; at the same time, titanium alloy TC4, P-BTO in comparative example 1, and pure titanium instead of BTO@TiO2 were used for comparison. The results are as follows Fig.14 shown.
[0119] Fig.13 In the figure, TC4 represents titanium alloy TC4, P-BTO in BTO comparative example 1, BTO@TiO2 represents BTO@TiO2 in Example 1, and Con represents a blank control without adding any coating material (containing only mouse embryonic osteoblast precursor cells (MC3T3-E1)).
[0120] Fig.14 US(-) indicates no ultrasonic stimulation; US(+) indicates ultrasonic stimulation, TC4 indicates titanium alloy TC4, Pure-BTO indicates P-BTO in comparative example 1, BTO@TiO2 indicates BTO@TiO2 in example 1, and Pure Ti indicates titanium.
[0121] from Fig.13 It can be seen that titanium alloy TC4, P-BTO in comparative example 1, and BTO@TiO2 in example 1 all show good biocompatibility; Fig.14 It can be seen that when US stimulation was added during the culture process, it was found that they all showed good biocompatibility, indicating that US stimulation had no significant effect on the whole process.
[0122] The role of bone implants with piezoelectric coatings in removing ROS and reshaping the bone regeneration microenvironment was further studied. First, mouse embryonic osteoblast precursor cells (MC3T3-E1) that play an important role in the bone repair process in mice were selected and co-cultured with titanium alloy TC4, P-BTO in comparative example 1, and BTO@TiO2 in example 1. After culturing for 3 days, 10ul of 10mM H2O2 was used to stimulate the cells with oxidative stress, and then placed in a cell culture incubator for 3 hours to ensure that the cells were in an oxidative stress state. Then, 1w / cm 2 US(1w / cm 2 After the US was completed, the supernatant was carefully discarded, the material was stained with cell nuclei and ROS detection kit, and the oxidative stress state of the cells co-cultured with the material was photographed under an upright microscope. The results are shown in Figures 15 to 17 .
[0123] from Fig.17 It can be seen that BTO@TiO2 in Example 1 completely eliminated the oxidative stress in the cells; Fig.16It can be seen that P-BTO in Comparative Example 1 cannot completely eliminate the oxidative stress in cells; Fig.15 It can be seen that the control group TC4 does not show the performance of removing oxidative stress. Therefore, the present invention successfully prepares the titanium alloy surface piezoelectric coating with antibacterial and oxidative stress removal properties.
[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A bone implant with a piezoelectric coating, characterized in that: It comprises a substrate and a piezoelectric coating located on the surface of the substrate, wherein the piezoelectric coating is a composite piezoelectric coating of barium titanate and titanium dioxide.
2. The bone implant with a piezoelectric coating according to claim 1, characterized in that The barium titanate is in a tetragonal phase, and the titanium dioxide is brookite-type titanium dioxide.
3. The bone implant with a piezoelectric coating according to claim 1, characterized in that The material of the substrate is any one of metal, metal alloy, hard alloy, silicon, glass and polymer.
4. The bone implant with a piezoelectric coating according to claim 3, characterized in that The metal includes any one of titanium, gold, platinum, niobium and tantalum; The metal alloy includes any one of titanium-based alloy, cobalt-based alloy, nickel-based alloy and stainless steel; The cemented carbide includes any one of tungsten carbide-based cemented carbide, titanium carbide-based cemented carbide, titanium carbonitride-based cemented carbide, and chromium carbide-based cemented carbide.
5. A method for preparing a bone implant with a piezoelectric coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: The barium carbonate and titanium dioxide are mixed and ball-milled to obtain a mixed powder; adding polyvinyl alcohol aqueous solution to the mixed powder, drying, grinding, and sieving to obtain spray powder; The spray powder is sprayed on a substrate by a plasma spraying method to obtain a bone implant with a piezoelectric coating.
6. The method for preparing a bone implant with a piezoelectric coating according to claim 5, characterized in that: The process parameters of the plasma spraying method include: argon flow rate of 40-60 L / min, hydrogen flow rate of 10-15 L / min, spraying power of 35-45 kW, spraying distance of 80-120 mm, and powder feeding rate of 18-25 g / min.
7. The method for preparing a bone implant with a piezoelectric coating according to claim 5, characterized in that: The molar ratio of barium carbonate to titanium dioxide is 1:(1-3); The ball milling medium used in the ball milling is zirconium oxide grinding beads; The ratio of the sum of the mass of the barium carbonate and the titanium dioxide to the mass of the ball milling medium is 1:(1-1.5); The ball milling speed is 350-400 r / min, and the ball milling time is 4-6 hours.
8. The method for preparing a bone implant with a piezoelectric coating according to claim 5, characterized in that: In the step of adding polyvinyl alcohol aqueous solution to the mixed powder, the mass concentration of the polyvinyl alcohol aqueous solution is 10-15%, and the mass of the polyvinyl alcohol aqueous solution is 5-10% of the mass of the mixed powder.
9. The method for preparing a bone implant with a piezoelectric coating according to claim 5, characterized in that: The mesh number of the spraying powder is 80 to 200 meshes.
10. Use of a bone implant with a piezoelectric coating as claimed in any one of claims 1 to 4 or a bone implant with a piezoelectric coating prepared by the preparation method as claimed in any one of claims 5 to 9 in the preparation of a biomaterial for promoting bone regeneration or in the generation of ROS or H2 under the action of ultrasound.